A REVIEW IN THE APPLICATION OF ARTIFICIAL INTELLIGENCE IN MANY MEDICAL SECTORS - Abeer Hadi Almotairi; Fahad Hamoud Alswegi; Mohammed Ghathith Almutairi; Fahad Saeed Falah Almotiry; Mishal Nayef Hamad Al Rakhimi; Albandry Hadi Matar Aljamily; Nasser Mashlaeh Mansor Aldosari; Rana Yaseen Alaoufi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Artificial Intelligence (AI) stands at the forefront of transformative technologies reshaping industries worldwide, and nowhere is its potential more pronounced than in the field of medicine. From revolutionizing clinical practice to enhancing diagnostics and patient management, AI holds the promise of unprecedented advancements in healthcare. Within this landscape, our research embarks on a journey to explore the intricate relationship between physicians and AI, delving into the nuanced perspectives from various medical specialties.The narrative unfolds against the backdrop of significant strides in cancer research propelled by AI. This cornerstone sets the stage for a broader examination of AI's impact across medical domains. We navigate through the imaginaries and tensions harbored by physicians regarding AI, deciphering their desires for seamless integration and alignment with established clinical workflows.Embedded within this exploration is the crucial concept of the 'clinician-in-the-loop,' where trust and contestability intertwine to ensure the responsible adoption of AI in medical practice. Physicians seek not only transparency but also control over AI systems, balancing the need for innovation with the preservation of their expertise.